The Implantation of Science, Technology and Society in Physics teaching at the Federal Institute of Maranhão: a methodological intervention proposal (Research, Society and Development, 2020)
The aim of this investigation is to analyze the assumptions of the CTS approach (Science, Technology and Society) as a methodological alternative to improve the learning of the Physics discipline of students at the Federal Institute of Education, Science and Technology of Maranhão (IFMA). The work was developed along the lines of field research. For data collection, the instruments used were: analysis of official documents proposing the curriculum for high school, exploratory questionnaire and conducting classes with the proposed approach. For the triangulation of the data we involved three categories of analysis: Aspects of the pedagogical practice related to the teaching methodologies of Physics; Relationship of students with the discipline of Physics; Students and the new teaching approach (CTS). According to the results obtained, it was found that the CTS approach is feasible to be implemented at IFMA as an alternative to improve teaching and learning of the exact subjects.